University-industry linkage and their interaction channels from the perspective of the academy, the industry and the public policies - Sarabia-Altamirano, Gabriela (Universidad Autónoma de Tamaulipas, 2016)
The university-industry linkage is a high impact factor on the economic development of countries, as it allows the knowledge and technology generated to be marketed for the benefit of society. For many years the indicators of success of these activities were patents, licensing and business generation (spin-off); however, informal channels of interaction have also been identified. Such channels often have more importance than formal interactions given their frequency and retribution. In this work the university-industry linkage, including the effect of public policies, was analyzed from the perspective of the main actors such as industry, university and researchers. The findings show that each actor brings different motivations and barriers that influence the establishment of interactions. Developing countries tend to use channels such as joint research, human capital formation and advisory services because of the context and areas of development that present their industry, as well as the level of research of their universities. Public policies are a key elements to promote the university-industry linkage, and they should be designed based on cultural patterns, types of firms and intensity of research activity in the territory. Archive XML (SciELO)